Post-Harvest Handling through Processing Oranges into Wine to Increase the Added Value of Oranges when Fruit is Abundant and the Skills of the Women Farmer Group "Widya Pertiwi" in Belantih Village, Kintamani District, Bangli Regency - Astiari, Ni Komang Alit; Sulistiawati, Ni Putu Anom; Suaria, I Nengah; Singapurwa, Ni Made Ayu Suardani; Sutapa, I Gede; Andriani, Anak Agung Sagung Putri Risa; Rama, Kade Nusde Sari (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2024)
The community service activity on aimed at post-harvest handling through processing citrus fruits into wine to increase the added value of citrus fruits when the fruit is abundant. And the skills of the farmer women's group "Widya Pertiwi" in Belantih Village, Kintamani District, Bangli Regency. This service activity is carried out through stages, namely providing material and demonstrations on processing oranges into wine and final evaluation (post-test) through distributing questionnaires. The results of counseling and training showed that through training and hands-on practice, they could easily understand how to process citrus fruit into wine, which could be done when the fruit was excessive in the harvest season, to increase added value and income. The results of this activity showed an overall increase in knowledge where 85% of respondents stated that they understood very well, and the remaining 15% indicated that they understood the extension materials and methods provided, which means that there were no respondents who stated that they did not understand or did not understand. Of the 15 respondents who participated in the counseling, 80% indicated they were very satisfied, and the remaining 20% stated they were satisfied participating in the counseling activities. 95% of the respondents indicated they were very interested, and the remaining 5% stated they were interested in practicing turning citrus fruits into wine in their homes. This means that 100% of the participants from the farmer women's group are interested in improving their skills and applying the technology of processing citrus fruits into wine to reduce the occurrence of fruit spoilage when the fruits are abundant in the harvest season.